2007
DOI: 10.1016/j.juro.2007.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Testicular Maturation Arrest to Testis Cancer: Spectrum of Expression of the Vitamin D Receptor and Vitamin D Treatment In Vitro

Abstract: To our knowledge this is the first description of vitamin D receptor in different primary testis pathologies and in an embryonal carcinoma cell line. The in vitro model showed that vitamin D receptor is an active receptor and it is inducible with the addition of vitamin D. Testosterone may be important for vitamin D receptor down-regulation. Calcium may be an important co-factor in vitamin D receptor expression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 13 publications
1
15
0
2
Order By: Relevance
“…The expression of VDR and vitamin D metabolising enzymes in human testis, ejaculatory tract and mature spermatozoa (12) suggests a potential role for vitamin D in spermatogenesis and spermatozoa maturation. Specifically, the observed cytoplasmic co-expression of the VDR and vitamin D metabolising enzymes (CYP2R1, CYP27A1 and CYP27B1) in Leydig cells suggests that vitamin D may be linked to male reproductive hormone functioning, although uncertainty remains as to the consistency of some of the immunohistochemistry data (12,31). The observation that VDR knockout mice develop hypergonadotrophic hypogonadism (32) also advocates a potential link between the vitamin D and HPT axes.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of VDR and vitamin D metabolising enzymes in human testis, ejaculatory tract and mature spermatozoa (12) suggests a potential role for vitamin D in spermatogenesis and spermatozoa maturation. Specifically, the observed cytoplasmic co-expression of the VDR and vitamin D metabolising enzymes (CYP2R1, CYP27A1 and CYP27B1) in Leydig cells suggests that vitamin D may be linked to male reproductive hormone functioning, although uncertainty remains as to the consistency of some of the immunohistochemistry data (12,31). The observation that VDR knockout mice develop hypergonadotrophic hypogonadism (32) also advocates a potential link between the vitamin D and HPT axes.…”
Section: Discussionmentioning
confidence: 99%
“…These observations suggest that curcuminoid-binding to cells activates signal transduction pathways that lead to dose- or time-dependent reductions in cell division, induction of senescence, or apoptosis. Indeed, curcumin has been identified as an activating ligand for the vitamin D receptor (VDR) [86], which is also highly expressed in NT2/D1 cells [87]. The intracellular VDR could potentially be accessed by curcuminoids via the same cell membrane receptor- or caveolae-mediated mechanisms that are also used to transport steroid hormones [88].…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that testosterone downregulates the VDR in testis cells (42). In cultured human osteoblasts, androgens increase 1a-hydroxylase, a key enzyme in vitamin D metabolism which converts 25(OH)D to the biologically more active form 1,25(OH) 2 D (43).…”
Section: Malesmentioning
confidence: 99%